América Latina en la competencia geopolítica de las grandes potencias en el siglo XXI (Ágora Journal, 2023)
The geopolitical changes driven by the United States, China, and Russia in the 21st century pose challenges for Latin America. To dispute the influence of the United States, China and Russia have deployed smart power strategies in their foreign policies towards the region. Moscow has aimed to establish strategic alliances with several Latin American countries, especially those that have been historically critical of the United States. Meanwhile, Beijing has deployed smart power by focusing on economic cooperation and strengthening political and cultural ties in its foreign policy towards Latin America. In the context of the competition between great powers, as seen in the trade conflict between the United States and China and in the tensions caused by the war in Ukraine between Russia and the Western NATO alliance, Latin America has gained greater geopolitical and geostrategic significance. Therefore, the pursuit of unity and integration has become a priority for the governments of the region within the global relations system.
Keywords: Geopolitics; smart power; Latin America